Surface roughening during slicing reduces iridescence - Lawrence, T.E.; Hunt, Melvin C.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We evaluated surface roughening during slicing as a way to decrease iridescence of pre-cooked cured beef bottom round, inside round, and eye of round roasts. Using a textured slicing blade surface decreased iridescence intensity and the area of iridescence compared to the control (smooth surface). Iridescence intensity and percentage of iridescent area was greatest in the eye of round, followed by the inside bottom round. Iridescence (both intensity and percentage of area) in sliced meat products can be reduced by using a meat-slicing blade with a textured face.
Keywords: Beef; Iridescence